Recent Aqueous Activity on Mars Evidenced by Transverse Aeolian Ridges in the Zhurong Exploration Region of Utopia Planitia. Issue 6 (28th March 2023) - Wang, Jiang; Zhao, Jiannan; Xiao, Long; Peng, Shuai; Zhang, Liang; Zhang, Zhixin; Gao, Antong; Qiao, He; Wang, Le; Zhang, Shiqi; Xiao, Xiao; Shi, Yutong; et al.
Abstract: Aqueous activities on Mars have gradually declined since the Noachian (>3.7 Ga). Although water can be stored in the subsurface during the latest epochs, geomorphological evidence is still limited. In this study, we used in situ imaging and spectral data acquired by China's Zhurong rover, as well as high‐resolution remote‐sensing data, to investigate the transverse aeolian ridges (TARs) in the Zhurong landing region of Utopia Planitia. A two‐stage evolutionary scenario of the TARs is proposed and polygonal features with hydrated minerals are identified for the first time on the surface of Martian TARs. We discussed the possible formation mechanisms of the polygonal features, and proposed that they could be related to recent aqueous activity and atmosphere‐surface water exchange on Mars, which sheds light on the hydrological cycle of Mars in current cold and dry climate. Plain Language Summary: The history of water on the surface of Mars has been studied for a long time. Since about 3.7 billion years ago, the role of water has gradually declined. Although the existence of subsurface ice on present‐day Mars has been confirmed, evidence for surface water is still limited. Transverse aeolian ridges (TARs), a kind of ripple‐like aeolian landform, are widely distributed on Mars and usually thought to be active within the last ∼3 million years. They are also identified in southern Utopia Planitia, the landing region of China's Mars exploration rover Zhurong. We analyzed the morphology and evolution of the TARs in the Zhurong landing region, and found some polygonal features with hydrated minerals such as gypsum on the surface of the latest‐formed TARs. We discussed the possible origins of these polygons, and proposed that they represent very recent aqueous activity on the Martian surface, which will help us better understand the hydrological cycle on current Mars. Key Points: Morphology and evolution of the transverse aeolian ridges (TARs) in the Zhurong landing region are studied Polygonal features with hydrated minerals are identified on some of the TARs investigated by the Zhurong rover The polygons could be related to very recent aqueous activity and atmosphere‐surface water exchange on Mars